If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying tan(2pi + x) = 0 (2ip * ant + x * ant) = 0 (2ainpt + antx) = 0 Solving 2ainpt + antx = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), 'ant'. ant(2ip + x) = 0Subproblem 1
Set the factor 'ant' equal to zero and attempt to solve: Simplifying ant = 0 Solving ant = 0 Move all terms containing a to the left, all other terms to the right. Simplifying ant = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(2ip + x)' equal to zero and attempt to solve: Simplifying 2ip + x = 0 Solving 2ip + x = 0 Move all terms containing a to the left, all other terms to the right. Add '-2ip' to each side of the equation. 2ip + -2ip + x = 0 + -2ip Combine like terms: 2ip + -2ip = 0 0 + x = 0 + -2ip x = 0 + -2ip Remove the zero: x = -2ip Add '-1x' to each side of the equation. x + -1x = -2ip + -1x Combine like terms: x + -1x = 0 0 = -2ip + -1x Simplifying 0 = -2ip + -1x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| h(x)=x^2-8ln-2 | | 8x+19=-28-8x | | -2w+8=-56 | | 5p^2+6p+1=O | | (y+9)2*2-(y+5)2*2=28 | | -7u-46=31 | | h(t)=-16t^2+36t+5 | | Y-8=2/3x | | 6d+57=39 | | 2x+3=2x-(3x+2x)+6 | | -6(-4x+3)-5x=7(x-2)-1 | | -5a+(-18)=22 | | -2(3+x)+3(2+2x)=1+4x | | 10x-3y-5x+13y= | | 10xsquare-3x-1=0 | | 2p-(-86)=52 | | 3600=200x-x^2 | | -4l+(-25)=55 | | 3x-13y=2forwhy | | 4(x-2)+2x=3(x-1)-11 | | -3e-72=-18 | | -214+-8(2x-3)=-334 | | 3v-36=-42 | | 10x+5=12y+5 | | 15y+20= | | 4r+(-12)=48 | | 15y/4=90 | | 2x-6+4x+28=6x+22 | | 3(x+1)x+4(x+3)=22 | | 4(2x-y)=2y+5 | | 147.1875=3r(3.14r^2) | | 0.4(x+25)-3=0.2(7x+10) |